Cyclodextrin subject-object recognition-based aptamer sensor for sensitive and selective detection of tetracycline - Wu, Yao-hui; Bi, Hao; Ning, Ge; Xu, Zheng-gang; Liu, Gao-qiang; Wang, Yong-hong; Zhao, Yun-lin (Journal of solid state electrochemistry, 2020)
Based on a β-cyclodextrin (β-CD) subject-object competition model, a simple and sensitive electrochemical aptamer sensor for the determination of tetracycline (TET) was fabricated. First, the TET aptamer modified with ferrocene (Fc) as a signal molecule was captured by β-CD loaded onto the gold electrode. Subsequently, TET was added to the detection system, causing a binding event between the target and aptamer with strong affinity during which process the aptamer configuration was changed from the original upright linear state to an agglomeration structure, resulting in its departure from the electrode surface. Consequently, an “off-signal” was turned along with the presence of the target. The results indicated that the TET concentration had a linear response to the signal ranging from 0.01 to 100 nM and the accurate detection limit could reach as low as 0.008 nM (3δ). The fabricated TET biosensor also showed outstanding detection specificity. Moreover, the suitability of the developed method was demonstrated in the determination of TET concentrations in different samples comprising water, milk, and bacteria culture medium, achieving acceptable recoveries for spiked samples ranging from 96.0 to 104.4%. This detection system was simple, economical, time-saving but remarkably sensitive, selective, and efficient, potentially rendering services in food safety screening and medical testing.